Tradisi Perang Timbung Dalam Menjaga Nilai-Nilai Sosial Berkelanjutan Pada Masyarakat Sasak Didesa Pejanggik - Habiratun Konsolehah (Politeknik Pariwisata Medan, 2024)
Pejanggik people carry out of Timbung War using glutinous rice mixed with coconut milk. This tradition contains quite strong social value of Pejanggik societies. This research aims to find out how the process of Timbung War and whar are sosial values contained in this tradition. The data collection techniques through observation, interview and documentation. The result of this research indicate that the Timbung War is one of traditions passed down by our ancestors which was carried out by generation to generation. The aim of Timbung War for rejecting bala’ and hoping for the blessing from God. The preparation of Timbung War begins with preparatory stage, consist of deliberation and consensus, preparing the equipment to be used. After that implementation stage, consist of taking of holy water, reciting zikir and barzanji, and asking permission to open the ceremony of Timbung War. Then, Clossing stage, consist of facial washing and forehead marking and then Timbung War.